Semiconductor Type Dependent Comparison of Electrical Characteristics of Pt/InP Structures Fabricated by Magnetron Sputtering Technique in the Range of 20–400 K - Korkut, H. (Nano-Micro Letters, 2013)
The paper describes how electrical properties of Pt/InP Schottky diode were affected by semiconductor type. We fabricated Pt/p-InP and Pt/n-InP Schottky diodes and measured electrical characteristics from 20 K to 400 K. Thicknesses of less than 30 nm of platinum were deposited on the two types of indium phosphide substrates using magnetron sputtering technique after the creation of Zn-Au ohmic back contact. We discussed basic diode parameters of idealiy factors, barrier heights and serries resistances of the two type of contacts. Additionly, unusual temperature characteristics of the the diodes were highlighted. These results were evaluated in terms of semiconductor type comparision of Pt/InP Schottky structures.